A realist review of residential treatment for adults with substance use disorder. (6th February 2023) - De Salis, Henry F.; Martin, Rachelle; Mansoor, Zara; Newton‐Howes, Giles; Bell, Elliot
Abstract: Issues: Completion of residential treatment for substance use disorder (SUD) relates to improvements in substance use and mental health. Findings from systematic reviews have been equivocal about which interventions work best for clients. There has been limited attention to the theories that explain the effectiveness of residential treatment. Approach: We conducted a realist review of the literature to identify program theories that would explain successful and unsuccessful outcomes from residential treatment for SUD. The unit of analysis was context–mechanism–outcome (CMO). Inclusion criteria were studies of residential treatment of more than 30 days for adults with SUD. Pharmacological studies were excluded. Key Findings: We identified 24 studies from 5748 screened. The studies were from settings comprising Indigenous programs, faith‐based programs, psycho‐social interventions and therapeutic communities and were conducted in North America, Scandinavia, Continental Europe and Australasia. We chose six CMO configurations as the best explanations for outcomes from residential treatment. Theories that best explained the mechanisms of change were the need to belong, meaning in life, and self‐determination theory. Implications: Previous research has noted similar outcomes from different residential treatment interventions, but has not been able to explain these similarities. In contrast, our findings suggest that the outcomes can be explained by causal mechanisms that apply across all programs, regardless of the philosophy of treatment. Conclusion: We identified six CMO configurations whose mechanisms of change could be explained by three overarching theories—the need to belong, meaning in life and self‐determination theory. The findings apply across ethnicities and genders.